1989
DOI: 10.1159/000310023
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Compatibility of Isovolaemic Haemodilution in the Treatment of Ischaemic and Non-ischaemic Central Retinal Vein Occlusion

Abstract: In a prospective study, 48 eyes with non-ischaemic and 35 with ischaemic central retinal vein occlusion (CRVO) were treated by isovolaemic haemodilution (IHD). Two or more cardiovascular risk factors were present in 42% of patients with non-ischaemic and in 69% of patients with ischaemic CRVO (p < 0.025). Nevertheless, IHD in no case caused serious cardiovascular complications. Minor problems were short fainting spells in 5% and a general weakness in 16% of the haemodiluted patients. The effect of IHD was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Conversion rates of 12.6% reported in other studies ranged from 0 [60] to 27% [61] during a follow-up varying from 10 weeks to 13 months after CRVO. The CVOS [55] reported that in the first 4 months of follow-up, 81 (15%) of 547 eyes with good perfusion converted to ischemia.…”
Section: Natural History Of Rvomentioning
confidence: 91%
See 1 more Smart Citation
“…Conversion rates of 12.6% reported in other studies ranged from 0 [60] to 27% [61] during a follow-up varying from 10 weeks to 13 months after CRVO. The CVOS [55] reported that in the first 4 months of follow-up, 81 (15%) of 547 eyes with good perfusion converted to ischemia.…”
Section: Natural History Of Rvomentioning
confidence: 91%
“…Hemodilution is expected to prevent the slowdown of blood circulation and its complications by dramatically lowering blood viscosity. Some randomized studies have been published on the topic and concluded on a statistically significant difference between treated and nontreated patients [61,79,80,81,82]. Nevertheless, these monocenter studies were conducted in the 1980s and 1990s, and they used different treatment protocols.…”
Section: Managementmentioning
confidence: 99%
“…Reducing the blood viscosity by different treatment modalities may well benefit the visual outcome. Several studies have demonstrated the beneficial effect of hemodilution on the visual acuity, and the retinal blood flow parameters in patients with CRVO [47][48][49]. In patients with markedly elevated fibrinogen concentration, one should consider additional therapy with fibrinogen reducing agents [50].…”
Section: Discussionmentioning
confidence: 99%
“…An impaired microcirculation and reduced blood flow lead to a dysfunction of the endothelial blood-retinal barrier with increased permeability and plasma exudation into the central retina. A causative therapy to normalize the retinal perfusion is desirable, but only hemodilution therapy has shown limited benefit in randomized studies [4,7,[12][13][14][15]31]. It seems reasonable to reduce the macular edema as soon as possible as irreversible damage of the photoreceptors occurs as early as 3 months after the development of macular edema [21,23].…”
Section: Introductionmentioning
confidence: 99%